Pengaruh Brand Image terhadap Keputusan Pembelian pada Smarthphone Samsung Galaxy A51 di Kecamatan Muara Bulian Kabupaten Batang Hari - Desi Trimeria Naibaho (Universitas Batanghari Jambi, 2021)
Samsung took the top spot from the report of 26.9% of market research firm IDC and report of market research firm Counterpoint. However, according to a report by market research firm Canalys, Samsung came in second. Samsung's smartphone sales in the last five years were 0.47%. Samsung has offered various types to the Indonesian market share, so that the Samsung Galaxy A51 is included in the top 5 best-selling smartphones in Indonesia based on a report by market research firm Omdia and Canalys at the end of 2020 in second place with sales of 11.4 million units. The purpose of this study was to determine the effect of brand image on purchasing decisions in Muara Bulian sub-district, Batanghari district. Brand image indicators include brand performance, brand social image, value received by consumers, consumer confidence in the brand, personal feelings towards the brand. While the indicators on purchasing decisions are the dimensions of quality and services, sales activities, after-sales service, company values. This study uses Primary and Secondary Data obtained from the results of distributing questionnaires to the people of Bulian District, Batanghari Regency who use the Samsung Galaxy A51 smartphone. And the data were analyzed by simple linear regression method. Samsung Galaxy A51 is a Galaxy series launched by PT. Samsung Electronics in December 2019. From the results of Simple Linear Regression with SPSS 20, the equation Y = 1.729 + 0.512X is obtained where the equation shows a positive influence between brand image on consumer purchasing decisions in Muara Bulian sub-district, Batanghari district, as evidenced by the regression coefficient which has an equation of 0.613. And the influence of brand image is 37.6% with the remaining 62.4% caused by other factors that are not researched that can influence purchasing decisions of the people of Muara Bulian sub-district, Batanghari district.